An Investigation of the Reliability of the Taiwan Earthquake Model PSHA2015 - Wang, Yu‐Ju (2017)
The Taiwan Earthquake Model (TEM) has had a new probabilistic seismic‐hazard analysis (PSHA) model for determining the probability of exceedance (PoE) of the ground motion over a specified period in Taiwan. We conducted several tests to investigate the adequacy of the seismic source parameters adopted by the TEM in 2015 (TEM PSHA2015). The observed maximal peak ground accelerations (PGAs) of the ML>4.0 mainshocks from 1993 to 2015 were used to test the predicted PGA from areal and subduction zone sources based on a time‐independent Poisson distribution. This comparison excluded the observations from the 1999 Chi‐Chi earthquake, because this was the only earthquake associated with the identified active fault in the testing period. We used tornado diagrams to analyze the sensitivities of these source parameters to the ground‐motion values of the PSHA. This study showed that the predicted PGA for a 63% PoE in the 23‐year period corresponded to observations, confirming the applicability of the parameters to areal and subduction zone sources. We adopted disaggregation analysis to determine the contribution of each seismic source to the hazard for six metropolitan cities in Taiwan. Sensitivity tests on the seismogenic structure parameters indicated that slip rate and maximum magnitude are the dominant factors in the TEM PSHA2015. For densely populated faults in southwestern Taiwan, the assessed hazard level is more sensitive to the maximum magnitude of earthquakes than it is to the slip rate of active faults, creating concern for the possibility of larger earthquakes due to multiple‐segment ruptures in this area, which has not yet been considered in the TEM PSHA2015. The source category disaggregation also suggested a seismic hazard over long periods in northern Taiwan due to subduction zone sources.